Accountability politics and development in colonial and post-colonial Africa : a case for democracy and federalism in Sub-Saharian Africa - Ijewere, Gabriel Oyaletor (Lagos, Nigeria : Primacy Limited, 1999)
A comprehensive and basic system study of accountability in governance and the priciple of management in public affairs. It is a call for democracy and Federalism in sub-Saharan Africa.
Includes bibliographical references and index.
oif 06/03/15
Loan
Keywords: Democracy; Responsibility; Africa, Sub-Saharan; Africa, Sub-Saharan; Africa, Sub-Saharan